Mathematics Algebra Number Theory 91357
Theory of Numbers : Fibonacci Number
Add
Remove

Suppose that F1 = 1, F2 = 1, F3 =1, F4 = 3, F5 = 5, and in general Fn = Fn-1 + Fn-2 for n ≥ 3 ( Fn is called the nth Fibonacci number .) Prove that F1 + F2 + F3 +...+ Fn = F(n + 2) - 1

Fibonacci numbers are investigated. The solution is detailed and well presented.

$2.19

Add to Cart
Remove from Cart

Solution provided by:
Thokchom Sarojkumar Sinha, MSc
About Expert

Education BSc, Manipur University MSc, Kanpur University Recent Feedback
"Thanks this really helped." "Sorry for the delay, I was unable to be online during the holiday. The post is very helpful." "Very nice thank you" "You are awesome. Thank you" "Thank you a million!!! Would happen to understand any of the other tensor problems i have posted???"